THE EMPLOYMENT OF PEOPLE AND SOCIO-ECONOMIC DEVELOPMENT OF REGIONS IN AZERBAIJAN - ISLAM HAGI, Ibrahimov; AGHAKISHIYEVA AGHAMOGHLAN, Nurana (Studia Universitatis Babes-Bolyai Studia Europaea, 2017)
The present article investigates the changes at demographic processes, factors of formation employment, socio-economic essence of ensuring employment in Azerbaijan. Ensuring stability in Azerbaijan, systematic measures carrying out in direction of reducing poverty and unemployment, opening new enterprises, Baku-Novorossiysk, Baku-Supsa, Baku-Tbilisi-Ceyhan oil pipelines and Baku-Tbilisi-Erzurum gas pipelines which play an important role in economy of Caucasus, essence of carrying out the project of TRASECA are explained. In article, the scientific-practical offers about carrying out the measures intended in the Strategic Road Map, the directions of the state regulation of employment and the socio-economic measures in regions are proposed.